2014
DOI: 10.1186/2050-7283-2-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between social capital and mental health and behavioural problems in children and adolescents: an integrative systematic review

Abstract: BackgroundMental health is an important component of overall health and wellbeing and crucial for a happy and meaningful life. The prevalence of mental health problems amongst children and adolescent is high; with estimates suggesting 10-20% suffer from mental health problems at any given time. These mental health problems include internalising (e.g. depression and social anxiety) and externalising behavioural problems (e.g. aggression and anti-social behaviour). Although social capital has been shown to be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
146
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 102 publications
8
146
3
2
Order By: Relevance
“…56 A growing body of evidence suggests that the presence and amount of social capital is essential for the health and successful development of young people. 79 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 A growing body of evidence suggests that the presence and amount of social capital is essential for the health and successful development of young people. 79 …”
Section: Introductionmentioning
confidence: 99%
“…1011 Some in the US argue that the rise of single parent households threatens these networks. 7 Researchers in the US 1213 and Europe 14 have shown that young people who grow up without both parents are disadvantaged over peers who do, and this effect persists when the effects of reduced economic resources are controlled. 15 Research documents similar findings in Latin America 16 and Africa, 1719 most visibly among orphans in sub-Saharan Africa, while in India, norms prescribing strict age and gender hierarchies within the family inhibit parent-child connections.…”
Section: Introductionmentioning
confidence: 99%
“…shared activities) (Ferguson 2006;R a l e y2014), perception of relationships with parents and teachers (e.g. being respected and treated fairly at home and school) (Goswami 2012;McAuley and Rose 2014;Rees and Main 2015), norms of reciprocity and trust at home and school (McPherson et al 2014), feeling of safety at home and school (Dufur et al 2015;Huebner et al 2014), and experience of being bullied (Klocke et al 2014). However, the existing evidence might have limited generalisability as most factors contributing to positive and negative child well-being so far identified in the field were based on western societies (with some exceptions, Kim and Main 2016;Re esetal .2016;Re es and Main 2015, See also: www.isciweb.org).…”
Section: Introductionmentioning
confidence: 99%
“…According to McPherson et al (2014) social capital is related to improved self-esteem, reduced psychological and behavioral problems, and improved quality of life. Social capital can be appeared within the relationship among close friends, family members and society members.…”
Section: Social Capital and Facebook Usagementioning
confidence: 99%